Impact of Improving Vehicle Front Design on the Burden of Pedestrian Injuries in Germany, USA, and India - Moran, Dane (Taylor and Francis, 2017)
European car design regulations and New Car Assessment Program (NCAP) ratings have led to reductions in pedestrian injuries. The aim of this study was to evaluate the impact of improving vehicle front design on mortality and morbidity due to pedestrian injuries in a European country (Germany) and 2 countries (the United States and India) that do not have pedestrian-focused NCAP testing or design regulations. Recent evaluations show a strong correlation between Euro NCAP pedestrian scores and real-life pedestrian injuries, suggesting that improved car front end design in Europe has led to substantial reductions in pedestrian injuries. Although the United States has fewer pedestrian crashes, it would nevertheless benefit substantially by adopting similar regulations and instituting pedestrian NCAP testing. The maximum benefit would be realized in low- and middle-income countries like India that have a high proportion of pedestrian crashes. Though crash avoidance technologies are being developed to protect pedestrians, supplemental protection through design regulations may significantly improve injury countermeasures for vulnerable road users.